Navigating the Waters: Exploring the Challenges and Strategies of Water Governance and Water Resource Management - Natalia Loseva (Social Science Chronicle)
Securing sustainable water supplies is a global imperative, and effective water quality management plays a pivotal role in achieving this goal. This comprehensive study evaluates the strategies and policies employed by six nations—Australia, Brazil, China, India, South Africa, and Sweden—in regulating water quality. It underscores the critical importance of water quality management for both ecosystems and human populations, emphasizing the urgent need for ongoing attention and efficient techniques. The study begins by highlighting the pressing challenges associated with water quality, including pollution, drought, and the impacts of climate change. It outlines the approaches taken by each of the six nations to address these issues. Australia has invested in infrastructure projects like the Snowy Mountains Scheme and the Murray-Darling Basin Plan to enhance water storage and transportation, bolstering water management across the country. Similarly, Brazil has pursued strategies like the Sobradinho Dam and the São Francisco River Integration Project, aimed at providing hydroelectric power and irrigation water for agriculture. China, on the other hand, has adopted a multifaceted approach to combat water pollution. This includes the implementation of a “river chief” system to oversee water resources, monitor water quality, and ensure its protection. India’s efforts to address water quality challenges include the construction of the Sardar Sarovar Dam and the ambitious Interlinking of Rivers Project, which aims to transfer water from water-rich to water-scarce regions while also generating hydroelectric power and supporting agriculture. The study concludes by acknowledging its limitations, particularly the scarcity of research on water quality management methods and regulations in many nations. It advocates for further investigation and cross-national comparisons to enhance our understanding of the effectiveness of water quality management systems. Additionally, the study recommends a comprehensive approach to water quality management that considers the intricate relationships between various industries and the environment.